The Colorful History of Active DNA Demethylation - Ooi, Steen K.T.; Bestor, Timothy H. (Cell, 2008)
Patterns of DNA cytosine methylation are subject to mitotic inheritance in both plants and vertebrates. Plants use 5-methylcytosine glycosylases and the base excision repair pathway to remove excess cytosine methylation. In mammals, active demethylation has been proposed to operate via several very different mechanisms. Two recent reports in Nature now claim that the demethylation process is initiated by the same enzymes that establish the methylation mark, the DNA methyltransferases DNMT3A and DNMT3B ( Kangaspeska et al., 2008; Métivier et al., 2008).